An Analysis of Unilateral Termination of Employment by Employers under Indonesia’s Manpower Law: Analisis Pemutusan Hubungan Kerja Secara Sepihak oleh Pengusaha Menurut Undang-Undang Ketenagakerjaan di Indonesia - Syahrana Kezia Anjunien Gunawan; Gunardi Lie (Academia Open, 2025)
General Background: Unilateral termination of employment (PHK sepihak) remains a persistent issue in Indonesia’s industrial relations, affecting workers’ economic and social stability. Specific Background: Despite the comprehensive regulation under Law No. 13/2003 on Manpower, gaps persist between legal norms and actual practices, particularly regarding procedural compliance and workers’ access to remedies. Knowledge Gap: Limited studies thoroughly examine how statutory provisions, post-MK decisions, and dispute-resolution mechanisms interact to shape the legality and consequences of unilateral termination. Aim: This study analyzes the legal framework governing unilateral termination, its legal consequences, and the protective mechanisms available to workers. Results: Findings show that unilateral termination is only lawful under conditions strictly regulated in the Manpower Law, including proven gross misconduct, corporate restructuring, or operational necessities, and must be accompanied by mandatory procedures such as negotiation and adjudication. Employers are obligated to provide severance, service appreciation pay, and compensation for rights, with variations depending on the grounds for termination. Novelty: This research integrates statutory analysis, judicial developments, and procedural safeguards to reveal persistent inconsistencies between legal standards and practical enforcement. Implications: Strengthening supervision, legal literacy, and procedural compliance is crucial to preventing arbitrary terminations and ensuring substantive worker protection. Highlights: The law strictly limits when employers may carry out unilateral termination. Workers are entitled to severance and other compensations based on legal provisions. Dispute-resolution mechanisms provide formal protection against arbitrary termination. Keywords: Unilateral Termination, Manpower Law, Worker Protection, Severance Rights, Industrial Relations